PEMANFAATAN MEDIA SOSIAL UNTUK MENINGKATKAN LAYANAN REFERENSI DI PERPUSTAKAAN PERGURUAN TINGGI - Ariska Oktavia (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
Introduction. This paper describes the use of social media to improve reference services at college libraries. Although the use of social media in college libraries has been extensively studied, there is still very little in the literature that focuses on the use of social media for reference services. Data Collection Method. The approach used in this study is a qualitative approach to obtain an in-depth overview of how social media can be applied to reference services. The source of this research data is library data. Analysis Data. The descriptive-analytical method in this study is intended as a research method whose sources are collected, analyzed and then interpreted critically then presented more systematically. Results and Discussions. Initially, social media was not fully believed to be used to improve library services in universities, indicated by apathy, lack of awareness and militant phobia. However, more and more college libraries are adopting social media in order to reach visitors through virtual space. Various kinds of interesting information can be posted by librarians. Through social media, users can get answers to specific questions. Conclusions. Social media can improve reference services to meet the unique and up-to-date information needs of visitors in the college library. But it needs to be socialized to the library users and training for librarians.